Friction and local pressure loss characteristics of a 5 × 5 rod bundle with spacer grids. (1st June 2020) - Ma, Zaiyong; Ye, Tingpu; Ren, Quanyao; Pan, Liangming; Bu, Shanshan; Zhang, Luteng; Sun, Wan
Highlights: Chun model would severely underestimate grid local loss coefficient for small Re . A two-phase friction multiplier correlation was first proposed for rod bundle. A new way to model the two-phase multiplier of spacer grid was proposed. Abstract: This paper presents the experimental results and analyses of the friction and local pressure loss coefficient of a 5 × 5 rod bundle with spacer grid. Based on the experimental data, friction and local pressure loss models were assessed and the role of spacer grid was discussed. The results showed that Cheng and Todreas model could predict bare rod friction loss well, and Chun model applied for high Re but would severely underestimate grid local loss for small Re . For two-phase condition, a universal correlation was proposed for bare rod two-phase friction multiplier, and it was found that all existing models cannot predict grid local loss multiplier very well. High prediction accuracy could be obtained by combining homogenous flow model, the liquid-mixture density ratio and a modification factor as a function of the grid parameter ε (axial projected area of grid strip to flow area) and void fraction.